THE IMPACT OF RELIGIOUS TOURISM IN THE SUNAN MURIA AREA ON THE ECONOMY AND SOCIAL CULTURE COLO DAWE KUDUS VILLAGE COMMUNITY - Via, Octaviana Azizah; Yusuf Falaq (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The purpose of the study was to describe the impact of religious tourism on the tomb of Sunan Muria on the social and economic life of the surrounding community and took the background in Colo Village, Dawe District, Kudus Regency. This study uses a form of qualitative exploratory research. The sample used is literature and previous research. While the technique of data collection is done by means of document analysis. To test the validity of the data the author uses the credibility of the method. Researchers used a qualitative analysis model and interactive analysis. Based on the results of this study, the existence of the Sunan Muria Tomb has an influence on the surrounding community, namely: changes in the social life of the community, including changing the status from unemployment to being unemployed, opening up business opportunities in the community, and also providing broad knowledge and insight for the community. While the impact in the economic field is certainly very large, namely an increase in financial income and also an increase in welfare for the economic life of the community.